EU identity as a factor of resilience in the face of Russia's special operation in Ukraine - Khakhalkina, Elena V. (Russia in global affairs)
The authors examine a close connection between the European Union's resilience and identity in academic and contemporary political discourse. In the latter case, the sources of the EU's resilience have not yet been identified, but the Russian factor has come as a variable that determines the connection between resilience and identity in the context of the Russia- Ukraine clash as a conflict of values. As a non-systemic challenge, Russia's special military operation (SMO) in Ukraine has shifted the focus in the EU's search for the sources of resilience and made it face the problems of self-identity in a changed environment. The article argues that the EU's collective identity may be a factor of its resilience. It concludes that, given the European Union's previous unsuccessful experience of appealing to collective identity in crisis situations, its use in the face of Russia's special military operation will be limited, although it has highlighted the need for strengthening the EU's identity.